2014
DOI: 10.1123/jpah.2011-0411
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Wrist-Based Cutpoints for the Actical Accelerometer in Elementary School-Aged Children

Abstract: This study established wrist-mounted Actical cutpoints for children using 2 methods. The differences in cutpoints and their effect on estimates of MVPA in an independent sample highlight challenges associated with establishing cutpoints, suggesting that standardized calibration procedures be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…The choice of which cut-points to use has implications for PA researchers looking to quantify MVPA or estimate the prevalence of those meeting the PA recommendation. Our study is in agreement with Schaefer et al (17) who used ROC and regression analyses to establish PA cut-points for the wrist using the Actical accelerometer. They then used a free-living sample to estimate the minutes of MPA and VPA and percent of participants meeting the PA recommendation of 60 minutes per day using both methods.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The choice of which cut-points to use has implications for PA researchers looking to quantify MVPA or estimate the prevalence of those meeting the PA recommendation. Our study is in agreement with Schaefer et al (17) who used ROC and regression analyses to establish PA cut-points for the wrist using the Actical accelerometer. They then used a free-living sample to estimate the minutes of MPA and VPA and percent of participants meeting the PA recommendation of 60 minutes per day using both methods.…”
Section: Discussionsupporting
confidence: 92%
“…However, only a few studies have addressed the wrist location. Specifically, the validity of algorithms for the Actical (1-axis; wrist) (7,17), Actiwatch (1-axis; wrist) (4), and GENEActiv (3-axis; wrist) (5,18) have been examined in the laboratory for children. Ekblom et al (4) showed that the Actiwatch accelerometer counts were significant correlated with EE (r = 0.80, p < 0.001) and Schaefer et al (18) demonstrated the ability of the GENEActiv to accurately classify SB and PA intensities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to development of tri-axial monitors, newer devices have been validated for wear on the wrist (61) , improving acceptability. Cut-points have been validated for MVPA for children (62) but data from hip-worn accelerometers should not be compared with wrist-worn accelerometers (63) , with discrimination between activity intensities better when worn on the hip rather than on the wrist (64) . Newer devices can output raw acceleration signals, offering promise for the future not only for quantification of physical activity but also pattern recognition.…”
Section: Recent Advances and Future Prospectsmentioning
confidence: 99%
“…Finally, compliance for the hip placement is lower in children, compared to adults, suggesting that other placements might be more feasible (Troiano et al, 2008). Recent studies have begun to examine the wrist more closely as an alternative placement in children (Schaefer, Nace, & Browning, 2013), overcoming concerns with data volume/integrity through 24-hour continuous data collection, however a major limitation to the wrist placement is the inability to capture activities involving locomotion. Finally, the ankle placement has not been extensively studied, yet may overcome many of the limitations of the hip site, through the opportunity for continuous, 24-hour data collection, and the limitations of the wrist site, through the ability to capture locomotion, a common form of physical activity.…”
mentioning
confidence: 99%
“…For the hip and wrist placements, these equations have been challenged and updated (Alhassan et al, 2012; R. C. Colley & Tremblay, 2011; Crouter et al, 2011; Hooker et al, 2012; Lyden, Kozey, Staudenmeyer, & Freedson, 2011; Rothney, Schaefer, Neumann, Choi, & Chen, 2008; Schaefer et al, 2013). The impetus for the current study was our laboratory’s experience applying the Actical manufacturer’s thresholds to ankle accelerometry data collected in free-living studies.…”
mentioning
confidence: 99%